The Influence of Schoology-Based Discovery Learning Model on Critical Thinking Ability in terms of Visual Spatial Intelligence - Lathifah Dewi Humairo; Budi Handoyo; Syamsul Bachri (Jurnal Pendidikan Humaniora, 2021)
Abstract: Currently, geography learning has not been able to develop students critical thinking skills. Critical thinking skills can be achieved through the learning used. This study aims to determine the effect of the schoological Discovery Learning model on critical thinking skills in terms of students' spatial visual intelligence. This is because intelligence is related to one's spatial perception. The design used was a quasi experimental with pretest and posttest research. Hypothesis testing uses two way annova analysis. The subjects in this study were students of class XI IIS SMA Al-Izzah Batu. The results showed that the schoological discovery learning model and spatial visual intelligence had an effect on critical thinking skills.Keywords: discovery learning, schoology, critical thinking skills, visual-spatial intelligence, geography learningAbstrak: Pembelajaran geografi saat ini belum mampu mengembangkan kemampuan berpikir kritis siswa. Kemampuan berpikir kritis dapat dicapai melalui pembelajaran yang digunakan. Penelitian ini bertujuan untuk mengetahui pengaruh discovery learning berwahana schoology terhadap kemampuan berpikir kritis ditinjau dari kecerdasan visual spasial siswa. Hal ini dikarenakan kecerdasan tersebut berhubungan dengan persepsi keruangan seseorang. Rancangan yang digunakan yaitu quasi experiment dengan desain pretest and posttest. Penelitian ini menggunakan analisis two way annova. Subjek penelitian ini adalah siswa kelas XI IIS SMA Al-Izzah Batu. Hasil penelitian menunjukkan model discovery learning berwahana schoology dan kecerdasan visual spasial berpengaruh terhadap kemampuan berpikir kritis.Kata kunci: discovery learning, schoology, kemampuan berpikir kritis, kecerdasan visual spasial, pembelajaran geografi